1979
DOI: 10.1099/00221287-115-1-161
|View full text |Cite
|
Sign up to set email alerts
|

Differing Contribution of Polymorphonuclear Cells and Macrophages to Protection of Mice against Listeria monocytogenes and Pseudomonas aeruginosa

Abstract: ~~ ~Bacterial growth and lethality of Listeria monocytogenes in mice were augmented by carrageenan-treatment and X-irradiation (8 J kg-l), whereas growth and lethality of Pseudomonas aeruginosa were augmented by X-irradiation but not by carrageenan-treatment. Protection against L. monocytogenes, at least in the early phases, appears to depend mainly on macrophages, since carrageenan depletes macrophages but not polymorphonuclear cells (PMN), whereas protection against P . aeruginosa appears to depend mainly on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0

Year Published

1982
1982
1997
1997

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(57 citation statements)
references
References 11 publications
3
54
0
Order By: Relevance
“…Protection against E. coli in normal mice is reported to depend mainly on PMN (23). In the present experiments, the functions of PMN in C. parvum-treated mice were not determined.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Protection against E. coli in normal mice is reported to depend mainly on PMN (23). In the present experiments, the functions of PMN in C. parvum-treated mice were not determined.…”
Section: Discussionmentioning
confidence: 58%
“…PMN are reported to be important for host resistance against Pseudomonas aeruginosa (24) and Escherichia coli (23), whereas macrophages playa protective role in the early stage of infection with Listeria monocytogenes (II).…”
mentioning
confidence: 99%
“…Since phagocytic cells, especially PMN, are known to be responsible for the primary protection in mice against E. coli and P. aeruginosa (17,18), further experi- ments were conducted to determine whether this compound affects the functional activities of phagocytic cells. In these experiments, we used BM 12,531 as a standard agent, because it is able to increase the number of leucocytes and their phagocytic activity (4,7).…”
Section: Effects Of Isohematinic Acid and Bm 12531 On Nbt Reduction mentioning
confidence: 99%
“…The resistance of normal mice against primary infection with P . aeruginosa seems to be attributable mainly to polymorphonuclear cells (PMN) but not to macrophages (Tatsukawa et al, 1979). On the other hand, complete Freund's adjuvant and BCG have been shown to activate mainly the functions of macrophages.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, which was carried out to determine the effect of BCG treatment in normal mice, it was found that BCG treatment did not augment the resistance but rather enhanced a lethal effect of pseudomonas infection. In addition such BCG treatment augmented the resistance against Listeria monocytogenes to which resistance had been reported to depend mainly upon the function of macrophages (Tatsukawa et al, 1979).…”
Section: Introductionmentioning
confidence: 99%